Study on the formation of magnetic nanoclusters and change in spin ordering in Co-doped ZnO using magnetic susceptibility1. Issue 81 (3rd September 2015) - Lee, Seunghun; Kim, Bum-Su; Park, Ji Hun; Lee, Tae-Woo; Chan Cho, Yong; Jeong, Se-Young
<x xml:space="preserve">Abstract</x> The temperature-dependent magnetic susceptibility measurement could provide a useful methodological approach as well as experimental clues for identifying the origin of magnetism in magnetic semiconductor.